Strategies of The Batam City Government in the Improvement of Illegal Urban Settlements: A Case Study on the Housing Quality Enhancement Program in Informal Areas - Krisman Hidayat Gea; Lubna Salsabila; Timbul Dompak; Iranda Firiansyah (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2024)
This research examines the strategies implemented by the Batam City Government in improving illegal urban settlements, with a focus on informal housing areas. The rapid urbanization and migration to Batam have led to the development of informal settlements, which often lack proper infrastructure, housing quality, and access to basic services. This study aims to assess the effectiveness of government programs aimed at improving these areas, particularly through initiatives focused on housing quality enhancement and urban planning. Through a case study approach, the research explores policy frameworks, stakeholder involvement, and community participation in the improvement process. The findings highlight key challenges and opportunities in addressing informal settlements, providing recommendations for better integration of these areas into the formal urban fabric. Ultimately, the research seeks to contribute to the understanding of sustainable urban development strategies for cities facing similar issues of informal settlement growth.